In Vitro Adhesion of Streptococcus Mutans to Polished IPS e.max and Feldspathic Porcelain - Ezatollah Jalalian; Ghazal Mofrad; Mohammad Rahbar; Afshin Mohseni; Mahshad Mohebbi (Islamic Dental Association of Iran, 2015)
Background and Aim: Finding appropriate dental materials with minimal adhesion and colonization of Streptococcus mutans (S. mutans) and other pathogenic bacteria is of great importance. The aim of this study was to compare the level of adhesion of S. mutans to polished IPS e.max and feldspathic porcelain and dental enamel. Materials and Methods: This in vitro experimental study was conducted on 15 specimens in three groups (five polished IPS e.max Press blocks, five polished feldspathic porcelain blocks and five dental enamel blocks) exposed to S. mutans bacterial suspension (1×106 mg/mL). The specimens were then rinsed twice and 0.1 mL of the new suspension was cultured on blood agar. After 48 hours of storage at 37˚C, S. mutans colonies were counted by naked eye. The results were analyzed using one way ANOVA. Results: The adhesion of S. mutans was 24.4±8.44 colonies/mm2 to the enamel, 5.6±2.35 colonies/mm2 to polished IPS e.max Press, and 5.8±1.92 colonies/mm2 to feldspathic porcelain. The difference between enamel and the other two groups in terms of adhesion of S. mutans was statistically significant (P<0.001); the two groups of ceramics were not significantly different in this regard (P=0.8). Conclusion: The adhesion of S. mutans to the enamel was higher than that to polished IPS e.max Press and polished feldspathic porcelain.